Retinal nerve fiber layer structure abnormalities in early Alzheimer's disease: Evidence in optical coherence tomography - Lu, Yan; Li, Zhen; Zhang, Xinqing; Ming, Baoquan; Jia, Jianping; Wang, Rong; Ma, Daqing (Neuroscience letters, 2010)
Alzheimer's disease (AD) patients often have visual disorders which may be due to retinal nerve degenerative changes. The aim of the current study was to determine the thickness changes of retina nerve fibers with optical coherence tomography (OCT) in AD patients. The OCT was used to assess the thickness of retinal nerve fiber layer (RNFL) from 22 AD patients and 22 healthy age-matched controls. The corrected visual acuity and intraocular pressure were measured and the dilated fundus examination and fundus image acquisition were also performed in those subjects. Compared with healthy age-matched controls, the RNFL thickness of AD patients were much thinner ( p < 0.05), especially in supra-retina and infra-retina, while no difference was found in the other retinal area. These changes were also confirmed by the fundus images. In conclusion, retinal nerve degeneration is present in the retina of AD patients and this degeneration is likely localized preferentially to the superior and inferior quadrant.